2021
DOI: 10.1186/s13075-021-02597-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic roles and therapeutic potential of the CCL8–CCR8 axis in a murine model of IgG4-related sialadenitis

Abstract: Background Our previous studies reveal that CCL18-CCR8 chemokine axis is upregulated in patients of immunoglobulin G4-related disease (IgG4-RD), suggesting that the CCL18–CCR8 axis is implicated in the etiology of IgG4-RD, although whether this axis has a potential as a therapeutic target remains unclear. Our purpose was to clarify the pathogenic roles and therapeutic potential of the murine CCL8 (analog of human CCL18)–CCR8 axis by using an animal model of IgG4-RD (LAT Y136F knockin mice; LAT … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…6 F). CCL1 and CCL18 produced by macrophages are known human CCR8 ligands with high affinity [ 23 ], and murine Ccl8 is a functional analog of human CCL18 [ 24 ]. Oxamate treatment decreased Ccl1 and Ccl8 expressions of tumor tissues from glioma implanted nude mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 F). CCL1 and CCL18 produced by macrophages are known human CCR8 ligands with high affinity [ 23 ], and murine Ccl8 is a functional analog of human CCL18 [ 24 ]. Oxamate treatment decreased Ccl1 and Ccl8 expressions of tumor tissues from glioma implanted nude mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furukawa S et al found that CCL18 was co-localized with massive infiltrated M2 in IgG4-RD affected tissues, and positively associated with the fibrosis scores (16). Honda F et al confirmed that blocking CCL8 (analog of human CCL18) in LAT Y136F knock-in mice (an animal model of IgG4-RD) alleviated the degree of fibrosis in affected salivary glands, and further in vitro assays revealed that CCL8 could directly stimulate collagen production in mouse fibroblasts (17). M2 can also induce plasma cell recruitment by secreting tumor necrosis factor ligand superfamily member 13(TNFSF13/APRIL) and further promote fibrogenesis (18).…”
Section: Non-t/b Lymphocyte-mediated Fibrosismentioning
confidence: 97%
“…2-mo-old Lat Y136F mice develop systemic autoimmunity as documented by the presence of autoantibodies directed to DNA and kidney and salivary gland autoantigens ( Genton et al, 2006 ; Sommers et al, 2002 ). Dense infiltrates made of CD4 + T cells and IgG1-producing plasma cells (PC) are found in the lung, liver, salivary glands, pancreas, kidney, and dura mater of Lat Y136F mice with occasional fibrosis and eosinophilia ( Aguado et al, 2002 ; Cui et al, 2019 ; Genton et al, 2006 ; Honda et al, 2021 ; Waseda et al, 2021 ; Yamada et al, 2018 ). In view of this spectrum of histopathological manifestations and considering that mouse IgG1 constitutes the homologue of human IgG4, it has been suggested that the Lat Y136F DLSP constitutes a mouse model of human IgG4-related disease (IgG4-RD; Yamada et al, 2018 ), a fibro-inflammatory condition originally characterized by high levels of IgG4.…”
Section: Introductionmentioning
confidence: 99%